Nowcasting durante la pandemia: Un apartado para Argentina - Emilio Blanco; Fiorella Dogliolo; Lorena Garegnani (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2022)
– We forecast economic activity in Argentina on a quarterly real-time basis using dynamic factors models (DFM) (Blanco et al. 2018) and evaluate their forecasting performance during the COVID19 pandemic of 2020. We compare the results of forecasts based on a pre-pandemic estimation of the parameters in the DFM and a re-estimated DFM with updated parameters using the most recent information. Considering the extreme observations that occurred during this particular year, we explore whether including new high frequency indicators (such as energy consumption and mobility) help capture more accurately the severe downturn.
Keywords: C22; C53; E37; 330; Wirtschaftsprognose; Coronavirus; Prognoseverfahren; Dynamische Wirtschaftstheorie; Faktorenanalyse; Schätzung; Argentinien